PENGARUH DIGITAL MARKETING DAN CUSTOMER RELATIONSHIP MARKETING TERHADAP LOYALITAS KONSUMEN THE BALI FLORIST - Savriana Wulandari; Anak Agung Putu Agung; Ni Putu Nita Anggraini (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2021)
The phenomenon that occurs in the era of the industrial revolution 4.0 at this time is the growing number of companies or entrepreneurs who sell online and take advantage of the Digital Marketing program. One of the businesses that are currently developing by utilizing Digital Marketing media is the Florist business. The purpose of this study is to determine the effect of Digital Marketing and Customer Relationship Marketing on Customer Loyalty in The Bali Florist. The population in this study were all members of The Bali Florist loyalty who lived in Bali, amounting to 565 people. The sampling method was randomized (accidental sampling). The number of samples used was 85 customers of The Bali Florist. The analysis technique used is the classical assumption test, multiple linear regression analysis and a model feasibility test consisting of the coefficient of determination, multiple correlation, F test, and t test. The results showed that: 1) Digital Marketing has a positive and significant effect on consumer loyalty of The Bali Florist. This means that the higher implementation of digital marketing will be able to increase consumer loyalty of The Bali Florist, and 2) Customer Relationship Marketing has a positive and significant effect on consumer loyalty of The Bali Florist. This means that the higher the implementation of Customer Relationship Marketing, the consumer loyalty of The Bali Florist will increase.